PENDIDIKAN KRITIS BERDIMENSI IDEOLOGIS KULTURAL - PUTERA SEMADI, ANAK AGUNG GDE (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dwijendra, 2018)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â In an effort to develop a critical education, the concept of education needs to be formulated as a process of cultural dimension / humanization process. The process of education can not be separated from human life in order to create cultural and cultural heritage (cultural creation and cultural transmission) to the young generation. Through the process of critical education, human beings are able to develop various potentials or creativity, taste, intention, and work that become the core of cultural process, because culture in the essential concept of education can be formulated as